The influence of magnesium preparations on the change in metabolism in the modeling of toxic nephropathy in animals - Pavliuk, N.; Badiuk, N. (Journal of Education, Health and Sport, 2022)
In an experiment on 39 white Wistar rats of autobred breeding, the authors modeled toxic nephropathy and assessed the possibility of correcting damage using magnesium-containing preparations - 5% Bischofite solution and «Donat Mg». The work was carried out in accordance with the regulatory documents of the European Union and Ukraine. The results of the studies showed that in addition to damage to the structure of the kidneys: wrinkling of capillary glomeruli, expansion of the Bowman space, destruction of part of the convoluted tubules; there is a violation of metabolic processes in the form of: an increase in the total blood protein, a redistribution of the proportion of different proteins in its composition, a decrease and imbalance of ATPases; increase in fasting amount of glucose; activation of lipid peroxidation and inactivation of AOD (catalase); decrease in magnesium levels in the blood. The use of magnesium-containing preparations by animals - a 5% solution of bischofite or «Donat Mg» had a unidirectional positive effect on the condition of the experimental animals. The structure of the kidneys improved, because. there were fewer wrinkled glomeruli, there were no lymphocytes between the capillaries, visually less damaged tubules were recorded; the interstitial layers did not differ from the norm; in terms of metabolism, there was a closeness of the total protein and the nomenclature of its components to the control, less changes in the activity of ATPases; LPO/AOZ systems; changes in fasting glucose, similarity of Mg+2 content to control data. The authors believe that the intake of exogenous Mg+2 has a positive effect on the state of redox processes in the cells of the body, which helps to maintain the body’s resistance at a higher level and prevents severe kidney damage.